2021
DOI: 10.2138/am-2021-7828
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of structural Fe(III) in nontronite by humic substances in the absence and presence of Shewanella putrefaciens and accompanying secondary mineralization

Abstract: Always consult and cite the final, published document. See http:/www.minsocam.org or GeoscienceWorld complexation capacity. A unique set of secondary minerals, including talc, illite, silica, albite, ilmenite, and ferrihydrite formed as a result of reduction. The results highlight the importance of coupled C and Fe biogeochemical transformations and have implications for nutrient cycling and contaminant migration in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 109 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…Iron-bearing smectites are practically ubiquitous in soils and sediments, where they can support microbial life and catalyze environmentally significant processes. Previous studies have established that FeRB can reduce Fe­(III) in smectite, ,, and resulting redox changes alter the reactivity of smectites toward metals and organic contaminants. ,,,, Our work showed that trioctahedral Fe­(II)-smectite can be used as an electron source to support the growth of a common, widely distributed microaerophilic Fe­(II) oxidizer. Biotic Fe­(II) oxidation may result in accelerated smectite Fe­(II) oxidation under some conditions but not others, and yet, in either case, smectite oxidation fuels growth.…”
Section: Discussionmentioning
confidence: 62%
“…Iron-bearing smectites are practically ubiquitous in soils and sediments, where they can support microbial life and catalyze environmentally significant processes. Previous studies have established that FeRB can reduce Fe­(III) in smectite, ,, and resulting redox changes alter the reactivity of smectites toward metals and organic contaminants. ,,,, Our work showed that trioctahedral Fe­(II)-smectite can be used as an electron source to support the growth of a common, widely distributed microaerophilic Fe­(II) oxidizer. Biotic Fe­(II) oxidation may result in accelerated smectite Fe­(II) oxidation under some conditions but not others, and yet, in either case, smectite oxidation fuels growth.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, they contribute to the creation of biogeochemical gradients, such as redox gradients in sediments and water columns ( Acosta-González and Marqués, 2016 ). Facultative bacteria are abundant in soil ( Table S1 in Supplementary material ), playing a crucial role in organic matter decomposition, element cycling, and the transformation of various compounds under changing oxygen conditions ( McNally et al, 1998 ; Grishchenkov et al, 2000 ; Cason et al, 2019 ; Zuo et al, 2021 ; Sheng et al, 2021a ; Dong et al, 2023a ). In anaerobic environments, such as wetlands and sediments, facultative anaerobes can make up a substantial proportion of the microbial community ( Bai et al, 2000 ; Zhu et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%